SIMPLE WAYS TO IMPROVE ENGLISH SPEAKING IN TEACHING AND LEARNING - Socheath, MAM (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
Most learners of English as Foreign Language find it difficult to deal with English Productive Skills–Speaking and Writing in effective ways. Because of the poor level ability in speaking and writing, students are failed to make an effective communication in English language. Some learners feel shy, even shameful, to speak in English as they are afraid of making mistakes. Instead, they usually use their own language while working in pair or group. It is noticed that many learners lack the confidence to speak in English, so we need to find ways of developing their communicative competence and motivate them through fun, stimulating, non-threatening activities. English Speaking is not too easy, not really difficult though. This paper will present some effective ways to help learners either build the better ability in English speaking or lead themselves toward better communication skills in English language. Additionally, the paper will demonstrate some funny and interesting speaking activities related to daily life communication as well as classroom activities. That will be helpful for both learners and teachers of English as Foreign Language.